1981
DOI: 10.1093/ajcn/34.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and aspirin depress prostaglandins in protection of chickens against Escherichia coli infection

Abstract: The hypothesis was tested that vitamin E protects chickens from a lethal Escherichia coli infection by inhibiting the biosynthesis of prostaglandins, thereby activating humoral immunity and phagocytosis. When chickens were fed supplement vitamin E at the level of 300 mg/kg diet, which is six times the presently used dietary level, endogenous PGE1, PGE2, and PGF2 alpha levels decreased in the immunopoietic organs, bursa, and spleen. Antibody titers to E. coli lipopolysaccharide and phagocytosis increased at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Mild chronic immune system stimulation was successfully achieved as numbers of WBC and serum TNF-α and PGE 2 concentrations measured on Days 14, 28, and 42 were greater compared with the baseline concentrations measured before the LPS injection on Day 0 in pigs fed a diet without any supplements. The acute phase response of immune system stimulation is characterized by the production of proinflammatory cytokines and PGE 2 , and under the conditions of this experiment, additive reductions in proinflammatory cytokines and PGE 2 were anticipated in pigs fed a diet supplemented with both Vit E and n-3 fatty acids, as Vit E and n-3 fatty acids are known to mitigate production of these compounds through independent mechanisms (Likoff et al, 1981;Wall et al, 2010;Kim et al, 2013). Conversion of the 18-carbon n-6 fatty acid arachidonic acid into PGE 2 is facilitated by transcription of cyclooxygenase-2 (COX-2) on signaling mechanisms through proinflammatory cytokines such as TNF-α or IL-1β (Rivest, 2010;Kalinski, 2012).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Mild chronic immune system stimulation was successfully achieved as numbers of WBC and serum TNF-α and PGE 2 concentrations measured on Days 14, 28, and 42 were greater compared with the baseline concentrations measured before the LPS injection on Day 0 in pigs fed a diet without any supplements. The acute phase response of immune system stimulation is characterized by the production of proinflammatory cytokines and PGE 2 , and under the conditions of this experiment, additive reductions in proinflammatory cytokines and PGE 2 were anticipated in pigs fed a diet supplemented with both Vit E and n-3 fatty acids, as Vit E and n-3 fatty acids are known to mitigate production of these compounds through independent mechanisms (Likoff et al, 1981;Wall et al, 2010;Kim et al, 2013). Conversion of the 18-carbon n-6 fatty acid arachidonic acid into PGE 2 is facilitated by transcription of cyclooxygenase-2 (COX-2) on signaling mechanisms through proinflammatory cytokines such as TNF-α or IL-1β (Rivest, 2010;Kalinski, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…tated in states of immune system stimulation (Likoff et al, 1981). However, recent evidence suggests that dietary levels of Vit E found in commercial pig diets are suboptimal and may limit adequate immune function (Sivertsen et al, 2007;Lauridsen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fraifeld et al (13) did not detect an increase in PGE 2 in the brain tissue of febrile chickens, and Nomoto (32) reported that, in pigeons, LPS seems to stimulate PG synthesis at peripheral sites only. It is clear that a contribution of PG to avian fever requires clarification, because PGs are known to regulate many physiological functions in birds, including circulation and respiration, which are closely related to thermoregulation (21,48).…”
mentioning
confidence: 99%
“…Beneficial effects on mortality and airsac lesions following experimentally induced colibacillosis were observed in broilers and turkeys by treatment with aspirine (acetylsalicylic acid) and sodium salicylate in doses equal to the dose used in the present study (Likoff et al 1981;Huff et al 2004). However, unexpectedly, in our study none of the NSAIDs showed a positive effect on colibacillosis lesions.…”
Section: Discussionmentioning
confidence: 69%
“…Medication doses and frequency were based on literature (Likoff et al 1981;Huff et al 1998Huff et al , 2004Baert and De Backer 2003;Jayakumar et al 2010). In order to maximize the chance of efficacy, drugs were administered long term, i.e.…”
Section: Introductionmentioning
confidence: 99%